Reconstructing the experienced temperature during the larval oceanic migration of anguillid eels from otolith stable oxygen isotopes - Mari Kuroki; Shunsuke Hayasaka; Kozue Nishida; Toyoho Ishimura; Akihiro Okamura; Yoshiaki Yamada; Yu-San Han; Kotaro Shirai (Scientific Reports)
Abstract Migration routes and the depth patterns of anguillid eel larvae migrating long distances from spawning grounds in the ocean remain poorly understood. We used otolith stable isotope analysis to study the oceanic migrations of anguillid eels by reconstructing experienced water temperature histories of larvae. The otolith stable oxygen isotopes (δ18Ootolith) of recruited Anguilla japonica glass eels were analyzed to assess the relationship with the experienced water temperature of the early larval stage in laboratory experiments. A negative linear relationship between rearing water temperature and δ18Ootolith values was observed for eel leptocephali reared at five different temperatures between 19 °C and 27 °C. Subsequently, the obtained equation between water temperature and δ18Ootolith was applied to estimate the water temperature experienced by wild-caught glass eels during their larval oceanic migration according to recruitment latitude, season, and species. The δ18Ootolith values of A. japonica glass eels were significantly higher at higher recruitment latitudes from Taiwan to Japan and later recruitment periods of 6 months, from November to March, indicating that the individuals were exposed to lower water temperatures along the Kuroshio flowing northward as they reached the higher latitudes in the later recruitment seasons. Furthermore, the δ18Ootolith values of the temperate A. japonica were higher than those of the tropical Anguilla marmorata, recruited at the same locations in southern Japan and Taiwan. This suggests that larval migratory behavior in the ocean may differ between the two eel species, although they have sympatric spawning areas in the western North Pacific. Collectively, these results suggest that δ18Ootolith provides a reasonable estimation of the experienced water temperature and may prove useful for reconstructing the early migratory history of anguillid eels in the ocean.